A Qualitative Analysis of Eating Behaviors Among Food Insecure College Students - Mooney, Grace; Drake, Teresa; Vollmer, Rachel L. (Journal of nutrition education and behavior, 2023)
To explore (1) how the cycle of food availability impacts food insecure college students’ food-coping behaviors and (2) how access to a campus food pantry impacts food availability. Qualitative, semistructured one-on-one interviews via Zoom were transcribed verbatim. Three investigators performed content analysis to identify and compare themes among participants with and without access to a campus food pantry. Forty undergraduate students from Illinois 4-year institutions with (n = 20) and without (n = 20) campus food pantries discussed similar experiences related to their food situation, eating behaviors, and use of resources, resulting in 7 themes: unique challenges of the college environment, childhood experiences, the impact of food insecurity, mental energy, the spectrum of resource management, structural barriers, and hiding hunger. Food insecure students may use coping mechanisms to manage food and resources. The existence of a campus food pantry alone is insufficient to meet the needs of these students. Universities could consider providing additional support (ie, free meals), advertising available resources, or integrating food insecurity screening into other established processes.